Adiponectin inhibits spontaneous and catecholamine-induced lipolysis in human adipocytes of non-obese subjects through AMPK-dependent mechanisms - Wedellová, Z; Dietrich, J; Siklová-Vítková, M; Kološtová, K; Kováčiková, M; Dušková, M; Brož, J; Vedral, T; Stich, V; Polák, J (Physiological research, 2011)
Adiponectin is an adipokine increasing glucose and fatty acid metabolism and improving insulin sensitivity. The aim of this study was to investigate the role of adiponectin in the regulation of adipocyte lipolysis. Human adipocytes isolated from biopsies obtained during surgical operations from 16 non-obese and 17 obese subjects were incubated with 1) human adiponectin (20 microg/ml) or 2) 0.5 mM AICAR - activator of AMPK (adenosine monophosphate activated protein kinase). Following these incubations, isoprenaline was added (10(-6) M) to investigate the influence of adiponectin and AICAR on catecholamine-induced lipolysis. Glycerol concentration was measured as lipolysis marker. We observed that adiponectin suppressed spontaneous lipolysis by 21 % and isoprenaline-induced lipolysis by 14 % in non-obese subjects. These effects were not detectable in obese individuals, but statistically significant differences in the effect of adiponectin between obese and non-obese were not revealed by two way ANOVA test. The inhibitory effect of AICAR and adiponectin on lipolysis was reversed by Compound C. Our results suggest, that adiponectin in physiological concentrations inhibits spontaneous as well as catecholamine-induced lipolysis. This effect might be lower in obese individuals and this regulation seems to involve AMPK.
Keywords: adiponektin; AMP-Activated Protein Kinases; obezita; Isoproterenol; Adipocytes; Obesity; tukové buňky; Humans; Lipolysis; mužské pohlaví; Male; lidé; proteinkinasy aktivované AMP; isoprenalin; lidé středního věku; Adiponectin; Middle Aged; lipolýza